Evaluación técnico-financiera para la desodorización de disolvente no. 4 (varsol), para el uso de una resina alquídica media (2019)
The present work focuses on the development of a deodorized No. 4 solvent, for use in the production of a medium alkyd resin, for Preflex SA, we worked with a national No. 4 solvent, obtained through the company EcopetroL, From this, a previous study was carried out, seeking to know what was the contaminants that had to be removed from the solvent to reduce its characteristic odor, the contaminant is known as mercaptan and is a union between sulfur and a CH bond, based on this A detailed search is carried out to select deodorization methods and raw materials to be used, investigating the reduction or elimination of these mercaptans.